Physiological effects of γ-aminobutyric acid application on cold tolerance in Medicago ruthenica - Li, Ying; Yu, Xiaojun; Ma, Kaikai (Frontiers in Plant Science, 2022)
Low temperatures in the seedling stage during early spring limit Medicago ruthenica germination and seedling growth. Elucidating the physiological mechanism of γ-aminobutyric acid (GABA)-regulated cold tolerance in M. ruthenica could provide a reference for alleviating the harmful effects of low temperatures on legumes in alpine meadows. The regulatory effects of GABA on M. ruthenica physiological parameters were explored by simulating the ground temperatures in the alpine meadow area of Tianzhu, China, in early May (2 h at 7°C; 6 h at 15°C; 4 h at 12°C; 2 h at 7°C; 10 h at 3°C). Our results showed that 15-mmol/L GABA was the optimal spray concentration to promote growth in the aboveground and belowground parts and increase the fresh and dry weight of seedlings. At this concentration, GABA enhanced the activities of catalase, peroxidase, superoxide dismutase, and ascorbate peroxidase, increased the osmotic balance, and inhibited the production of harmful substances in the cells under low-temperature conditions. GABA also regulated the tissue structure of leaves, increased the cell tense ratio, maintained photochemical activity, increased the amount of light energy to the photochemical reaction center, and improved the photosynthetic rate. Furthermore, exogenous GABA application increased the endogenous GABA content by promoting GABA synthesis in the early stages of low-temperature stress but mainly participated in low-temperature stress mitigation via GABA degradation in the late stages. Our results show that GABA can improve the cold tolerance of M. ruthenica by promoting endogenous GABA metabolism, protecting the membrane system, and improving the leaf structure.